Antibodies : a laboratory manual - Greenfield, Edward A.
"The focus of Antibodies: A Laboratory Manual, 2nd Edition, will be unchanged from the original edition by Ed Harlow and David Lane and will cover both the production and use of antibodies in a way that is accessible to the nonimmunologist. The emphasis will be on contemporary, essential antibody-based methods that are tried, true, necessary, and useful to a broad population of life scientists. The manual will provide up-to-date protocols that work reproducibly, along with explanations as to how and why methods work and how to choose between alternative approaches. Methods that have become research staples since the manual was originally published will be included at the same level of detail and organization as the existing topics"--